Rapid Diagnostic Testing for SARS-CoV-2 - Drain, Paul K (The New England journal of medicine, 2022)
RDTs for SARS-CoV-2 — either molecular nucleic acid amplification tests or antigen-based immunoassays to detect proteins — are approved for persons with Covid-19 symptoms and asymptomatic persons with known exposure to SARS-CoV-2 or those in a high-transmission setting. Antigen-based tests have lower sensitivity than PCR tests, but they may correlate better with replication-competent virus.